Comercialización y cooperación : inevitables en el cooperativismo oleícola - Adoración Mozas Moral; Olga Senise Barrio; Francisco José Torres Ruiz; Manuel Parras Rosa (TRABAJO. Revista Iberoamericana de Relaciones Laborales, 2000)
Sin resumen